Answer:
B. x=2wy+y-1
Explanation:
The given equation is
![(2x+2)/(y)=4w+2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f8qay7ylmdonotuo4x14vjfoele3cwxe1h.png)
We multiply through by y
![\implies y * (2x+2)/(y)=y(4w+2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fynf30jc2c6zuhuy99lknjwg4eswqejv3y.png)
![\implies 2x+2=y(4w+2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/s9w7tnqm94kei7mg794t6jkayimtw60lsv.png)
Moreover,we expand the parentheses at the right side of the equation to get
![\implies 2x+2=4wy+2y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/seik816hdlnctbzsjngw26sp2mpj62iyfk.png)
we then subtract 2 from both sides of the equation to arrive at
![2x=4wy+2y-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qfxa18facpz6tmzrdnsq67eu8uhe79qzyl.png)
we finally divide through by 2
![(2x)/(2)= (4wy)/(2)+ (2y)/(2)-(2)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/gsy3rwj2yayfwhot8atdtreclmlv4kpdh3.png)
![\implies x=2wy+y-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xo7yso3v48zw0lockiboytclx63zt7p73d.png)
Therefore the value of x=2wy+y-1